Neurotic Personality Traits and Risk for Adverse Alcohol Outcomes: Chained Mediation through Emotional Disorder Symptoms and Drinking to Cope. (24th August 2018) - Chinneck, A.; Thompson, K.; Dobson, K. S.; Stuart, H.; Teehan, M.; Stewart, S. H.; ,
ABSTRACT: Background : Rates of alcohol abuse are high on Canadian postsecondary campuses. Individual trait differences have been linked to indices of alcohol use/misuse, including neurotic traits like anxiety sensitivity (AS) and hopelessness (HOP). We know little, though, about how these traits confer vulnerability. AS and HOP are related to anxiety and depression, respectively, and to drinking to cope with symptoms of those disorders. Neurotic personality may therefore increase risk of alcohol use/abuse via (1) emotional disorder symptoms and/or (2) coping drinking motives. Objectives : Allan and colleagues (2014) found chained mediation through AS- generalized anxiety -coping motives-alcohol problems and AS- depression -coping motives-alcohol problems. We sought to expand their research by investigating how emotional disorder symptoms (anxiety, depression) and specific coping motives (drinking to cope with anxiety, depression) may sequentially mediate the AS/HOP-to-hazardous alcohol use/drinking harms relationships among university students. Methods : This study used cross-sectional data collected in Fall 2014 as part of the Movember-funded Caring Campus Project ( N = 1, 883). The survey included the SURPS, adapted DMQ-R SF, and AUDIT-3. Results : AS and HOP were both related to hazardous alcohol and drinking harms via emotional disorder symptoms and, in turn, coping drinking motives. All indirect pathways incorporating both mediators were statistically significant, and additional evidence of partial specificity was found. Conclusions/Importance : The study's results have important implications for personality-matched interventions for addictive disorders.